2020
DOI: 10.1111/eip.12966
|View full text |Cite
|
Sign up to set email alerts
|

Addressing cognitive health in coordinated specialty care for early psychosis: Real‐world perspectives

Abstract: Aim Addressing cognitive health during the early phase of psychosis has the potential to enhance recovery outcomes, yet methods to assess and treat cognitive problems are not a systematic part of Coordinated Specialty Care (CSC) in the United States. We sought to understand how CSC providers perceive cognitive health and gauge the acceptability and appropriateness of cognitive interventions to inform the development and implementation of a cognitive health toolkit for OnTrackNY, a CSC program. Methods Electron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…The current study provides some insights into the cognitionfocused treatments that young people with mental illness may find (Allott, van-der-el, et al, 2020); however, few trials have tested the effectiveness of compensatory interventions with young people, especially those with high prevalence conditions. Notably, research in early psychosis settings, which often serve a high proportion of young people with cognitive impairment, has found that compensatory interventions and psychoeducation are considered by clinicians to be the most feasible treatments to deliver (Saperstein et al, 2020;Saperstein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current study provides some insights into the cognitionfocused treatments that young people with mental illness may find (Allott, van-der-el, et al, 2020); however, few trials have tested the effectiveness of compensatory interventions with young people, especially those with high prevalence conditions. Notably, research in early psychosis settings, which often serve a high proportion of young people with cognitive impairment, has found that compensatory interventions and psychoeducation are considered by clinicians to be the most feasible treatments to deliver (Saperstein et al, 2020;Saperstein et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…While this observation may partly explain the discrepancy between the young people's cognitive needs and the provision of suitable treatments, it may also highlight a need for further workforce development. Supporting clinicians to routinely conduct cognitive screening and implement strategies with young people may be an important first step in addressing this need (Bryce & Allott, 2019; McIntyre et al, 2019; Saperstein et al, 2020; 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Service provision relies on shared decision‐making, using the assessment results as a reference. A menu of cognitive health services recognizes that no one approach to cognitive health is right for all persons and accounts for the variable resources, knowledge and interests reported by OnTrackNY teams (Saperstein et al, 2020). The menu includes psychoeducation for program participants and for family members (Medalia & Revheim, 2002), compensatory skills training (Twamley et al, 2003) and a restorative approach to cognitive remediation (Medalia & Saperstein, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…In a program evaluation study conducted with 22 OnTrackNY teams operating in a diverse array of healthcare settings (Saperstein et al, 2020), we found that cognitive health assessment and treatment practices ranged in type as well as frequency. Importantly, while providers identified numerous facilitating factors that would support the adoption of such practices, lack of knowledge of how to discuss cognitive health emerged as a significant barrier.…”
Section: Introductionmentioning
confidence: 92%